Indapamide: quantum-chemical properties - Kazakova, O. A.; Dovgan, R. S.; Syrova, G. O.; Zahorodnyi, M. I.; Chekman, I. S. (Reports of the National Academy of Sciences of Ukraine, 2016)
By the method of DFT (B3LYP/6-31G (d, p)) with the use of the solvation model IEF PCM (GAMESS), the electronic structure and energy characteristics of the indapamide in an aqueous solution are studied. The basic reaction centers of the molecule that can participate in the complexation are revealed. A nitrogen atom of the sulfanilamide group has the largest excess of the electron density, and a carbon atom of the carbonyl group has the largest positive charge.